Desacordos teóricos na filosofia do direito contemporânea: a influência da filosofia da linguagem no debate Hart-Dworkin e a tentativa de sua superação através da teoria dos planos de Scott Shapiro - RODRIGUES, Filipe Augusto Oliveira (Universidade Federal do Pará, 2018)
This work has as general objective to analyze the influence of philosophy of language on the Hart – Dworkin Debate and the overcoming tried by the planning theory of Scott Shapiro, focusing the theoretical disagreements. This objective is always sought by the mixture of two elements. In the first place, the exploration of the existing arguments in legal theory. Secondly, the relation of these arguments to those presented in fields of general philosophy. Our hypothesis is that the study of this debate and relationship show us that Dworkin's theory of disagreements is the best explanation of the problem, but at the same time the opposing theories chosen are using several methodological elements that represent advances that have been made in general philosophy, such as the perspective of the plans proposed by Michael Bratman. We attempt to demonstrate this hypothesis through the principal analysis of four authors and their influences, namely Ronald Dworkin, H.L.A. Hart, Jules Coleman, and Scott Shapiro. Through this analysis we hope to demonstrate how the foundations of the proposed theories have been changing the focus from philosophy of language to other fields and which is the state of legal theory with this advance. As result, we defend the point that the hypothesis is right and even without the best explanatory capacity, the new theories of law need to be better analyzed and their earnings better considered.